Evaluation, educational policy reforms, and their implications for arts education. Issue 3 (3rd July 2019) - Aróstegui, José Luis
Abstract: This article is the introduction to the special issue about Evaluation, Educational Policy Reforms, and Their Implications for Arts Education. A summary of all the articles comprised in the special issue is reported, mainly featured, on the one hand, by a discussion about how the education policy reforms shape a particular approach to evaluation that ends up conforming education and arts education and, on the other hand, it shows some magnet examples of arts curriculum evaluation combining both standardized assessment with qualitative strategies pertinent to the nature of arts content and experiences. The article also discusses how it could be possible to move from the current scope of school arts education most of the authors depict to the development of another way of evaluation and curriculum development where the experiential process is taken into account. While these signals might be still scarce, for some other authors could be the opportunity to overcome at least partially the current demise of school arts curriculum.